The Role of Student Engagement as a Mediator in Quality of School Life Among Low-Income Students - Rismawati, Rismawati; Latifa, Rena (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2026)
This study aims to address the research gap regarding the mechanisms that explain how classroom environment, parental involvement, and academic self-efficacy influence the quality of school life among students from low-income backgrounds through the mediating role of student engagement. The study sample consisted of 467 high school students in Indonesia. This study employed a quantitative approach using path analysis, while the construct validity of the instruments was tested using confirmatory factor analysis (CFA). The results indicate that classroom environment, academic self-efficacy, and student engagement collectively account for 53% of the variance in the quality of school life. Furthermore, classroom environment, academic self-efficacy, and parental involvement account for 43% of the variance in student engagement. Student engagement was found to significantly mediate the relationship between classroom environment, parental involvement, and academic self-efficacy on quality of school life. These findings expand our understanding of the role of student engagement as a psychological mechanism linking school, family, and individual factors to the quality of school life among students from low socioeconomic status families. The implications of this study suggest that schools and parents need to collaborate to enhance student engagement by creating a supportive learning environment and strengthening students’ academic self-efficacy.